The Competition among Fish Species Based on Types of Food in Buyan Lake, Bali, Indonesia - Shanti Paramita Jayanti; Pande Gde Sasmita Julyantoro; Gde Raka Angga Kartika (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Buyan Lake is located in Bali Province, this lake has a variety of fish species which several of those species are introduced species that called as alien fish. The relationship interaction between native fish and introduced fish can be described based on the study of food habit and competition of food types. The study was conducted from January to March 2018. Types of fish caught in Buyan Lake during the study were 7 species of fish namely Oreochromis niloticus, Amatitlania nigrofasciata, Osteochilus vittatus, Cyprinus carpio, Xiphophorus hellerii var. 1, Xiphophorus hellerii var. 2, and Rasbora lateristriata. The results showed that the fish with the highest ISC value was Amatitlania nigrofasciata, while the fish with the lowest ISC (Index of Stomach Content) value was Xiphophorus hellerii var. 1. The standard deviation range of almost all fish species is close to zero, so it is suspected that the contents of the stomach are nearly similiar. Amatitlania nigrofasciata with the highest standard deviation values are thought to have a variety of gastric contents. Based on the analysis of the contents of the stomach content, Oreochromis niloticus, Osteochilus vittatus, and Xiphophorus hellerii var. 2 are belonging to herbivorous fish. While Amatitlania nigrofasciata, Cyprinus carpio, Xiphophorus hellerii var. 1, and Rasbora lateristriata are belonging to omnivorous fish, which are tending to herbivores. The competition of food type is quite strict, there is similarity of food among species of fish in Buyan Lake, which is mean that they are fighting over the same food resources.